Assessment and follow-up of interstitial lung disease - Devarasetti Phani Kumar (Indian Journal of Rheumatology)
Patients with suspected interstitial lung disease (ILD) clinically presenting with cough and breathlessness are initially investigated with a chest radiograph and spirometry. The finding of a normal or increased forced expiratory volume in 1 second (FEV1)/forced vital capacity (FVC) ratio in the presence of reduced FVC on spirometry should alert for the presence of a restrictive defect and the need to order for complete lung function tests, including lung volumes and diffusion capacity of the lungs for carbon monoxide (DLCO) and 6-minute walk test (6MWT). High-resolution computed tomography (HRCT) is required to identify the specific patterns. To determine a more specific diagnosis, serology for connective tissue diseases, bronchoalveolar lavage, and a lung biopsy are needed. A multidisciplinary approach involving the pathologist, rheumatologist, pulmonologist, and radiologist allows the correlation of the clinical, radiologic, and pathologic findings to arrive at the right diagnosis. Screening guidelines based on expert opinion are available for idiopathic pulmonary fibrosis (IPF) and non-IPF ILDs (sarcoidosis, hypersensitivity pneumonitis, and systemic sclerosis). Follow-up monitoring for progression based on risk factors is mandatory for the early identification and management. Symptom assessment, a decline in pulmonary function tests (forced vital capacity [FVC], DLCO, and 6MWT) and worsening fibrosis on HRCT give clues for progression. The monitoring schedule in progressive fibrosing ILD for repeat pulmonary function tests is between 3 and 6 months and for HRCT is 12–18 months in the appropriate clinical context. An individualized approach to repeat pulmonary function tests and HRCT in stable ILD is required.